β-Ecdysterone Enhanced Bone Regeneration Through the BMP-2/SMAD/RUNX2/Osterix Signaling Pathway - Yan, Cai-Ping; Wang, Xing-Kuan; Jiang, Ke; Yin, Chong; Xiang, Chao; Wang, Yong; Pu, Chaoyu; Chen, Lu; Li, Yu-Ling (Frontiers in Cell and Developmental Biology, 2022)
Bone defects are a global public health problem. However, the available methods for bone regeneration are limited. In recent years, the application of traditional Chinese herbs for bone regeneration has attracted increasing attention. β-ecdysterone is a herbal extract similar to estrogen that promotes the metabolism of cell protein synthesis; however, its function on bone regeneration is not yet clear. In this study, we investigated the function of β-ecdysterone on osteoblast differentiation and bone regeneration in vitro and in vivo. MC3T3-E1 cells were used to test the function of β-ecdysterone on osteoblast differentiation and bone regeneration in vitro. The results of the CCK-8 assay suggested that the proliferation of MC3T3-E1 cells was promoted by β-ecdysterone. Furthermore, β-ecdysterone influenced the expression of osteogenesis-related genes, and the bone regeneration capacity of MC3T3-E1 cells was detected by PCR, the alkaline phosphatase (ALP) test, and the Alizarin Red test. β-ecdysterone could up-regulate the expression of osteoblastic-related genes, and promoted ALP activity and the formation of calcium nodules. Moreover, we also determined that β-ecdysterone increased the mRNA and protein levels of components of the BMP-2/Smad/Runx2/Osterix pathway. DNA sequencing further confirmed these target effects. β-ecdysterone promoted bone formation by enhancing gene expression of the BMP-2/Smad/Runx2/Osterix signaling pathway and by the enrichment of biological processes. For in vivo experiments, the femur condyle defection model was constructed by drilling a critical-sized (3×3 mm) defect in 12-week-old SD male rats to further assess the bone regeneration functions of β-ecdysterone. The results of micro-CT showed that β-ecdysterone could accelerate bone regeneration and exhibited higher bone volume, bone surface, bone mineral density at each observation time point. Immunohistochemistry confirmed that the β-ecdysterone also increased the expression of collagen, osteocalcin, and BMP2 in the experiment group at 4 and 8 weeks. In conclusion, discovered β-ecdysterone is a new bone regeneration regulator that can stimulate MC3T3-E1 cell proliferation and induce bone regeneration through the BMP-2/Smad/Runx2/Osterix pathway. This new function of β-ecdysterone has revealed a new direction of osteogenic differentiation and has provided novel therapeutic strategies for treating bone defection.